(untitled) (International Seven Journal of Multidisciplinary, 2023)
The field of hair enhancement has undergone significant transformation with the advancement of hair extension techniques. This article explores the most used methods—clip-in, tape-in, sew-in, fusion, and micro-link—and critically assesses their limitations in terms of durability, scalp health, and aesthetic integration. Drawing from dermatological and cosmetic science literature, the discussion highlights how conventional approaches often compromise hair integrity and realism. Additionally, it examines the sociocultural and economic factors driving the demand for more discreet and damage-free solutions. The article concludes by presenting innovative alternatives that employ biomimetic materials and personalized application methods, offering more natural, durable, and health-conscious solutions for hair extension users.